Aberrant anaplastic lymphoma kinase expression in high-grade pulmonary neuroendocrine carcinoma. Issue 8 (25th April 2013) - Nakamura, Harumi; Tsuta, Koji; Yoshida, Akihiko; Shibata, Tatsuhiro; Wakai, Susumu; Asamura, Hisao; Furuta, Koh; Tsuda, Hitoshi
Abstract : Aims: In lung cancer with anaplastic lymphoma kinase ( ALK ) gene rearrangement, accurate diagnosis is essential to identify patients who can be treated with a specific kinase inhibitor. Sensitive ALK immunostaining can provide nearly complete concordance with gene rearrangement status and is expected to serve as a surrogate biomarker for tailored treatment with an ALK inhibitor. In the present report, we describe aberrant ALK expression in a small proportion of pulmonary neuroendocrine carcinomas (NECs) that do not have ALK gene alteration. Methods: A total of 227 pulmonary NECs were assembled on tissue microarrays and were subjected to highly sensitive ALK staining methods. Results: We observed focal positivity with heterogeneous intensity in 2 (2.9%) of 69 small-cell carcinomas and 1 (0.9%) of 106 large-cell NECs. In contrast, 52 carcinoid tumours were all negative for ALK expression. Neither ALK rearrangement nor amplification was observed using fluorescence in situ hybridisation, and no somatic mutation was detected in three ALK positive NECs. Conclusions: Thus, this aberrant expression is probably of a wild-type ALK and a potential pitfall when implementing sensitive ALK immunohistochemistry in the molecular diagnosis of lung cancer.